A retrospective analysis of Laos's Nam Theun 2 Dam. Issue 2 (3rd March 2020) - Scudder, Thayer
ABSTRACT: I was appointed in 1997 at the start of the World Bank's independent International Environmental and Social Panel of Experts for the Nam Theun 2 Dam. I made over 20 visits to Laos to carry out our analyses, before resigning in March 2014. This article concentrates on the Nakai Plateau resettlement and, where relevant, the dam's Watershed Management and Protection Area, which included a large area between the future reservoir and the Vietnam border. It includes what I consider the main mistakes that were made during the resettlement process on the Nakai Plateau.